Effects of Explants Division by Cutting, Concentrations of TDZ and Number of Sub-culture Cycles on Propagation of ‘Kluai Hom Thong’ Banana in a Temporary Immersion Bioreactor System - Daungban, Sarisa; Pumisutapon, Paweena; Topoonyanont, Nopmanee; Poonnoy, Poonpat (Thai Journal of Science and Technology, 2017)
Abstract Banana is an industrial fruit crop for which there is strong demand in export markets. Because of disease problems in growing areas, there is a need for more pathogen-free planting materials. To develop a system for propagating bananas in a temporary immersion bioreactor (TIB) we studied factors affecting the number of new shoots formed by Musa (AAA group) ‘Kluai Hom Thong’ in a 700-ml twin-flasks TIB with liquid medium supplied for 2 minutes a time every 4 hours, in comparison to the same types of explants cultured in a conventional semi-solid medium system. We compared leaving the explants uncut or longitudinally cutting them into 2 or 4 sections and tested adding thidiazuron (TDZ) at the concentrations of 0, 0.125 and 0.250 mg l-1), for 3 culture cycles of 6 weeks each. The results showed that the most effective combination was cutting the explants in 4 sections and culturing in TIB with 0.125 mg l-1 TDZ, which resulted in up to 11.03 new shoots per explant in the third culture cycle. The number of shoots per container increased to 48 and 132 in the second and third cycles, respectively, or 2.08 and 5.74 times more than the number of shoots per container in the first cycle (23). Bananas cultivated in the semi-solid medium system developed fewer new shoots per container and a larger percentage of small-sized shoots. Keywords: micropropagation; apical dominance; thidiazuron; subculturing